2020
DOI: 10.1080/16184742.2020.1780289
|View full text |Cite
|
Sign up to set email alerts
|

Comparing competitive balance between genders in team sports

Abstract: Research question: Interest in women's team sports has increased over time. However, there is still little research comparing competitive balance between genders in the bigger sports leagues. Against this background the main research question is whether there are systematic differences in competitive balance between the genders among the bigger sports leagues. Research methods: The analysis involves football (soccer), handball and basketball leagues for the period 2007/08-2016/17 (14 leagues and 135 observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…By contrast, the WNBA seems to be more balanced than the NBA, despite more males playing basketball than females in North America. Kringstad (2021) suggested that this is due to the lower number of teams in WNBA (12 vs. 30 in NBA), consistent with the need for an optimal number of teams to ensure CB.…”
Section: Competitive Balance and Gender Studiesmentioning
confidence: 83%
See 2 more Smart Citations
“…By contrast, the WNBA seems to be more balanced than the NBA, despite more males playing basketball than females in North America. Kringstad (2021) suggested that this is due to the lower number of teams in WNBA (12 vs. 30 in NBA), consistent with the need for an optimal number of teams to ensure CB.…”
Section: Competitive Balance and Gender Studiesmentioning
confidence: 83%
“…More recently, Kringstad (2021) compared the level of CB (measured through win dispersion, performance persistence and championship concentration) between genders in the football and handball championships from three European countries (England, France and Germany), while extending the scope of his study to North American basketball, i.e., the men's National Basketball Association (NBA) and its women's counterpart (WNBA). Results show significantly lower CB for women than men in football and, to a lesser extent, in handball, consistent with the previous literature.…”
Section: Competitive Balance and Gender Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the NHL tied games occurred up to 2004 and are treated as half wins in the RSD and %Time, while point percentages is used in the ASD*. The approach adopted by Kringstad (2021) for applying ASD* to the NBA is used, with ASD ub calculated each season using the end-of-regular-season standings to rank teams and with the notional distribution of win percentages for the perfectly competitive dominated league outcome calculated on the basis of the actual match schedule for the given season. We follow the suggestion in Utt and Fort (2002), based on Fort and Quirk (1997), that competitive dominance can be conceptualised as the best team winning all matches, while the second-best team wins all of its matches except the those against the best team and so on (see also Competitive balance in the NA major leagues Horowitz, 1997;Owen, 2010).…”
Section: Technical Appendixmentioning
confidence: 99%
“…Some studies have considered women's sport from a broader economic perspective (e.g. Kringstad, 2021; Scelles, 2021; Valenti et al ., 2020a, 2020b). However, these papers centre competitive balance, and this is not the focus of our paper.…”
mentioning
confidence: 99%